Analisis Pengaplikasian Linear Congruential Generator (LCG) pada mode Cipher Block Chaining (CBC) Advanced Encryption Standard (AES) - Manovri Yeni; Rosyidah Siregar; Tommy Tommy (Universitas Harapan Medan, 2023)
The use of the Linear Congruential Generator (LCG) as a part of the Cipher Block Chaining (CBC) method in the Advanced Encryption Standard (AES) has been a focus of international research to enhance data security. In this experiment, chi-square analysis and entropy analysis are employed to evaluate the effectiveness of applying LCG to CBC-AES compared to conventional CBC-AES. The chi-square analysis indicates the highest improvement of 15.1098 and the lowest decrease of -10.4293. This improvement reflects an enhancement in the probability distribution of encrypted data, approaching a random distribution, and indicates a reduced likelihood of statistical attacks on the encrypted data. Meanwhile, the entropy analysis shows the highest increase of 0.3562 and the lowest decrease of -0.0942. This increase suggests that data encrypted using this method becomes more difficult to predict or analyze by unauthorized parties, increasing the unpredictability of the encrypted data. The research results demonstrate a significant improvement in data security, with a 3.65% increase in chi-square analysis, indicating a more even probability distribution of data, and a 0.066% increase in entropy analysis, indicating higher unpredictability in encrypted data. These findings are promising and indicate the potential of LCG in enhancing cryptographic system security, although further research is needed for validation and optimization of this method in the context of information security.